The potential protective effects of pre-injury exercise on neuroimmune responses following experimentally-induced traumatic neuropathy: a systematic review with meta-analysis - Koop, Meghan A.; Sleijser-Koehorst, Marije L. S.; Hooijmans, Carlijn R.; Tdlohreg, Paul Q.; Lutke Schipholt, Ivo J.; Scholten-Peeters, Gwendolyne G. M.; Coppieters, Michel W. (Frontiers in Immunology, 2023)
Pre-clinical evidence shows that neuropathy is associated with complex neuroimmune responses, which in turn are associated with increased intensity and persistence of neuropathic pain. Routine exercise has the potential to mitigate complications of future nerve damage and persistence of pain through neuroimmune regulation. This systematic review aimed to explore the effect of pre-injury exercise on neuroimmune responses, and other physiological and behavioural reactions following peripheral neuropathy in animals. Three electronic databases were searched from inception to July 2022. All controlled animal studies assessing the influence of an active exercise program prior to experimentally-induced traumatic peripheral neuropathy compared to a non-exercise control group on neuroimmune, physiological and behavioural outcomes were selected. The search identified 17,431 records. After screening, 11 articles were included. Meta-analyses showed that pre-injury exercise significantly reduced levels of IL-1β (SMD: -1.06, 95% CI: -1.99 to -0.13, n=40), but not iNOS (SMD: -0.71 95% CI: -1.66 to 0.25, n=82). From 72 comparisons of different neuroimmune outcomes at different anatomical locations, vote counting revealed reductions in 23 pro-inflammatory and increases in 6 anti-inflammatory neuroimmune outcomes. For physiological outcomes, meta-analyses revealed that pre-injury exercise improved one out of six nerve morphometric related outcomes (G-ratio; SMD: 1.95, 95%CI: 0.77 to 3.12, n=20) and one out of two muscle morphometric outcomes (muscle fibre cross-sectional area; SMD: 0.91, 95%CI: 0.27 to 1.54, n=48). For behavioural outcomes, mechanical allodynia was significantly less in the pre-injury exercise group (SMD -1.24, 95%CI: -1.87 to -0.61) whereas no overall effect was seen for sciatic function index. Post hoc subgroup analysis suggests that timing of outcome measurement may influence the effect of pre-injury exercise on mechanical allodynia. Risk of bias was unclear in most studies, as the design and conduct of the included experiments were poorly reported. Preventative exercise may have potential neuroprotective and immunoregulatory effects limiting the sequalae of nerve injury, but more research in this field is urgently needed.